Dimethyl Itaconate‐Loaded Nanofibers Rewrite Macrophage Polarization, Reduce Inflammation, and Enhance Repair of Myocardic Infarction. Issue 17 (14th March 2021) - Nakkala, Jayachandra Reddy; Yao, Yuejun; Zhai, Zihe; Duan, Yiyuan; Zhang, Deteng; Mao, Zhengwei; Lu, Linrong; Gao, Changyou
Abstract: Cellular metabolism plays a major role in the regulation of inflammation. The inflammatory macrophages undergo a wide‐range of metabolic rewriting due to the production of significant amount of itaconate metabolite from cis‐aconitate in the tricarboxylic acid cycle. This itaconate molecule has been recently described as a promising immunoregulator. However, its function and mode of action on macrophages and tissue repair and regeneration are yet unclear. Herein, the itaconate‐derivative dimethyl itaconate (DMI) suppresses the IL‐23/IL‐17 inflammatory axis‐associated genes and promotes antioxidant nuclear factor erythroid 2‐related factor 2 target genes. The poly‐ε‐caprolactone (PCL)/DMI nanofibers implanted in mice initially maintain inflammation by suppressing anti‐inflammatory activity and particular inflammation, while at later stage promotes anti‐inflammatory activity for an appropriate tissue repair. Furthermore, the PCL/DMI nanofiber patches show an excellent myocardial protection by reducing infarct area and improving ventricular function via time‐dependent regulation of myocardium‐associated genes. This study unveils potential DMI macrophage modulatory functions in tissue microenvironment and macrophages rewriting for proper tissue repair. Abstract : Poly‐ε‐caprolactone (PCL)/dimethyl itaconate (DMI) nanofibers maintain the particular inflammation at the initial stage while increased the anti‐inflammation at the later period. The PCL/DMI nanofibers patches efficiently reduce fibrosis and protect myocardial functions by regulating inflammation‐associated genes, blood clotting factors, calcium metabolism, glucose transport, anti‐apoptosis, matrix metalloproteases, and gap junction pathways.